Care and Commitment in Ethical Consumption: An Exploration of the ‘Attitude–Behaviour Gap’ - Shaw, Deirdre (Journal of business ethics, 2016)
In this paper we argue that greater attention must be given to peoples’ expression of “care” in relation to consumption. We suggest that “caring about” does not necessarily lead to “care-giving,” as conceptualising an attitude–behaviour gap might imply, but that a closer examination of the intensity, morality, and articulation of care can lead to a greater understanding of consumer narratives and, thus, behaviour. To examine this proposition, a purposive sample of self-identified ethical consumers was interviewed. Care is expressed by the study’s participants in a variety of ways and linked to behaviour through diverse patterns that includes consumption and abstention. We find significant correspondence between the academic literature on the ‘ethics of care’ and our participants’ articulation of their ethical consumption behaviours. We suggest, therefore, that a close understanding of an ethics of care among consumers is important both in providing insight into the attitude–behaviour gap challenge evident in the literature and to the continued development of an ethical consumption discourse.